(untitled) (Journal of the College of Basic Education, 2023)
The aim of the research is to identify the interactive e-learning and to identify the quality of university teaching and to identify the relationship between interactive e-learning and the quality of university teaching. The researchers used the descriptive analytical method in collecting opinions, information, facts and concepts related to the research axes, in order to build an integrated knowledge system, in which the research problem, its background, importance and objectives become clear, by referring to a number of studies, research and articles, and reviewing some global experiences in the field of interactive e-learning and education. The blended, to benefit from it in presenting what it referred to about the aspects related to the concept of blended education, its application, its quality assurance, its success criteria and its benefits in the educational process. The second axis: the overall quality in education and standards and quality assurance requirements for interactive e-learning. The third axis: Interactive e-learning models and its success factors, features and obstacles The fourth axis: How to design an interactive e-learning program The first axis: e-learning, e-learning and university teaching One of the most important conclusions of the research is that the only solution It is the focus on education, whatever its level, the quality of its curricula and methods, and finding ways to solve its problems, and since the human being is the inexhaustible renewable natural wealth, and it is one of the main inputs to the educational process, its axis and its outputs, with its culture away from the manifestations of imitation and alienation, given that its outputs It is represented in the development of human resources in its various scientific, cultural, economic and social aspects. As for the recommendations of the research, it was a review of university programs and curricula and strategies for their implementation, in order to assimilate the concepts of the electronic and technological revolution, integrate them with teaching methods of high quality, and present them to students, in a manner that fulfills the requirements of creativity and innovation. It meets the needs of the people D and the community. E-learning is a dear demand for all educational circles, but the high costs, the large number of requirements and the complexity of its procedures, prevent the possibility of its full application in the educational process, which allows for the application of one of its types, such as interactive e-learning.